2021
DOI: 10.56082/annalsarscibio.2021.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds from Plants Used as Therapeutic Agents in Biomedical Applications – a Literature Review –

Abstract: This review proposes an extensive study of some bioactive compounds produced by plants (piperine - PIP, curcumin - CUC, resveratrol – RES, icariin - ICA) with beneficial effects on human health. In addition to these compounds, the need for natural pigments, carotenoids in the body's daily diet and implicitly in nano-science and medicine is also debated. This study points to complexes of proactive compounds as well as their interaction with other drugs (e.g., doxorubicin: DOX, 5-fluorouracil: 5-FLU, paclitaxel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 156 publications
0
2
0
Order By: Relevance
“…The previous study carried out by our team showed a rich biological activity and therapeutic potentials of piperine, curcumin, resveratrol, and icariin. Also, we discussed the interaction between them, the interaction with chemotherapeutic drugs, the interaction with silver and gold nanoparticles and the beneficial effects on health, especially applications in cancer cell lines [1].…”
Section: Fig 1 Bioactive Compounds From Plantsmentioning
confidence: 99%
“…The previous study carried out by our team showed a rich biological activity and therapeutic potentials of piperine, curcumin, resveratrol, and icariin. Also, we discussed the interaction between them, the interaction with chemotherapeutic drugs, the interaction with silver and gold nanoparticles and the beneficial effects on health, especially applications in cancer cell lines [1].…”
Section: Fig 1 Bioactive Compounds From Plantsmentioning
confidence: 99%
“…Curcumin is a vegetable compound widely exploited for its biological activities. Since its bioavailability, bioactivity, stability and physico-chemical behavior are less effective, strategies have been developed to improve curcumin properties by complexing with whey proteins [65][66][67][68], betacyclodextrin [69][70][71][72][73][74] with natural compounds such as piperine , silymarin, resveratrol [75,76], lipids and hydroxyapatite. Due to their unique properties, nanoparticles have found various uses in many fields starting from hydrogen production [77][78][79][80][81][82], synteses of materials with photoluminescence proprieties [83], adsorption capabilities [84,85], photocatalytic proprieties [86] to bio materials [34][35][36][37][38].…”
Section: Composite Materials Based On Hydroxyapatite 41 Hydroxyapatit...mentioning
confidence: 99%